2018
DOI: 10.4103/ijpsym.ijpsym_169_17
|View full text |Cite
|
Sign up to set email alerts
|

Attitude toward Selfie Taking and its Relation to Body Image and Narcissism in Medical Students

Abstract: Background: The recent and rapidly popularized social phenomenon of selfie taking has been showing an increasing trend. It is thus imperative to assess the knowledge, attitude, and perception of the groups toward this phenomenon. Selfie taking is associated with younger age groups and hence, we aimed to explore the attitudes toward selfie taking and its relation toward body image and narcissism in medical college students. Methodology: This was cross-sectional study and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…At the same time, postgraduate males scored much higher in body image acceptance than undergraduate males. People who were more satisfied with their body image posted more confident selfies to Instagram, according to their research [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, postgraduate males scored much higher in body image acceptance than undergraduate males. People who were more satisfied with their body image posted more confident selfies to Instagram, according to their research [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further research found that body image dissatisfaction is closely linked to depression, eating disorders, and low self-esteem [ 17 , 18 ]. Certain study revealed that people who were more satisfied with their body image posted more selfies to Instagram confidently showing off [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers who attempt to examine selfies within the framework of dramaturgy often relate the selfie to the production of body image-making (Dutta et al, 2018). The formation of body image through the selfie cannot be separated from the creation of the self.…”
Section: A Dramaturgic Approach: the Selfie As Self-presentationmentioning
confidence: 99%
“…As selfies become a new form of digital culture, scholars have begun to examine questions relating to the motivations that shape the digital activities of selfie‐taking and selfie‐posting. Recent studies have generally focused on the psychological dispositions that underpin the phenomenon of selfie‐taking and selfie‐posting (Biolcati & Passini, 2018; Dutta et al, 2018; Sorokowski et al, 2015). Biolcati and Passini (2018), for example, relate the selfie‐taking and selfie‐posting behavior to narcissism and poor self‐esteem.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral addictions are addictions to activities or processes such as gambling, eating, tanning, sexuality, and shopping. These types of addiction may be more common in more youthful age group [1].…”
Section: Introductionmentioning
confidence: 99%